Association Between the Epidemiological Profile and the Heart Electrical Function of Patients with Chagas Disease - Dias, Lineker Fernandes; Oliveira, Stefan Vilges de (JOURNAL OF CARDIAC ARRHYTHMIAS, 2022)
Objective: To analyze the association between the epidemiological profile and cardiac electrical function in patients with Chagas disease. Method: This is a descriptive, cross-sectional study, based on the analysis of medical records from a teaching hospital in Minas Gerais. The association of the epidemiological characteristics of the individuals included in the study with the results of their ECGs was analyzed. Results: 70 medical records were evaluated. Most of the sample was elderly (81.42), with a predominance of males (47.14%), and white ethnicity (50%). Left bundle branch blocks (18.57%) and left and right bundle branch blocks (11%), left ventricular overload (71.43%) and secondary changes in ventricular repolarization (21.43%) were the predominant electrophysiological changes. When checking the association between the epidemiological profile and cardiac electrical function, the only significant association was between the variables ethnicity and atrioventricular blocks (AVB). Conclusion: Among the residents of Minas Gerais with CD, elderly white men likely tend to develop AVB.